2004
DOI: 10.1038/sj.bjp.0705652
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the mouse cold‐menthol receptor TRPM8 and vanilloid receptor type‐1 VR1 using a fluorometric imaging plate reader (FLIPR) assay

Abstract: 1 TRPM8 (CMR1) is a Ca 2 þ -permeable channel, which can be activated by low temperatures, menthol, eucalyptol and icilin. It belongs to the transient receptor potential (TRP) family, and therefore is related to vanilloid receptor type-1 (VR1, TRPV1). We tested whether substances which are structurally related to menthol, or which produce a cooling sensation, could activate TRPM8, and compared the responses of TRPM8 and VR1 to these ligands. 2 The effects of 70 odorants and menthol-related substances on recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
333
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(365 citation statements)
references
References 45 publications
21
333
2
3
Order By: Relevance
“…Published EC 50 values for activation of TRPM8 are, in order of potency, 0.2 Ϯ 0.1 M (icilin) Ͼ 5.9 Ϯ 1.6 mM (geraniol) Ͼ 6.7 Ϯ 2 mM (linalool) Ͼ 7.7 Ϯ 2 mM (eucalyptol) (6). No response was observed upon application of icilin (20 M) or eucalyptol (3 mM) at 33°C (Fig.…”
Section: Pharmacological Properties Ofmentioning
confidence: 93%
“…Published EC 50 values for activation of TRPM8 are, in order of potency, 0.2 Ϯ 0.1 M (icilin) Ͼ 5.9 Ϯ 1.6 mM (geraniol) Ͼ 6.7 Ϯ 2 mM (linalool) Ͼ 7.7 Ϯ 2 mM (eucalyptol) (6). No response was observed upon application of icilin (20 M) or eucalyptol (3 mM) at 33°C (Fig.…”
Section: Pharmacological Properties Ofmentioning
confidence: 93%
“…Transient receptor potential melastatin 8 (TRPM8), a membrane receptor involved in calcium ion influx and cell signal transduction (Behrendt et al, 2004;Bautista et al, 2007), is over-expressed in melanoma cells and some other types of cancer, such as prostate, breast and colorectal cancers (Zhang and Barritt, 2006;Johnson et al, 2009;Faridi et al, 2011), although in untransformed cells TRPM8 is mainly found in sensory neurons and some epithelial cells, and plays a role in cooling sensation (Bautista et al, 2007;Sabnis et al, 2008;Banner et al, 2011). Although there is a suggestion that TRPM8 is related to tumoriogenesis and cancer cell physiology (Zhang and Barritt, 2006;Prevarskaya et al, 2007a;2007b), there is only limited evidence to support this idea.…”
Section: Dose-dependent Cytotoxic Effects Of Menthol On Human Malignamentioning
confidence: 99%
“…Several reports show that menthol triggers an increase in cytosolic Ca 2+ levels (Behrendt et al, 2004;Yamamura et al, 2008;Kim et al, 2009), leading to downstream Ca 2+ -dependent cell signaling pathways. With respect to its bioactivity, some studies have recently reported on the efficiency of menthol in killing cancer cells such as gastric, leukemia, prostate, colorectal adenocarcinoma and skin (melanoma) cancers (Lin et al, 2005;Lu et al, 2006;Yamamura et al, 2008;Kim et al, 2009;Lu et al, 2009;Faridi et al, 2011), but few studies have pointed out a mechanism.…”
Section: Dose-dependent Cytotoxic Effects Of Menthol On Human Malignamentioning
confidence: 99%
“…In the past, several small molecules (Figure 1) have been reported to show TRPM2 inhibitory activity with variable IC 50 (1.2~76 μ m ), including flufenamic acid (FFA),18, 19 2‐(3‐methylphenyl) aminobenzoic acid (3‐MFA),19 N ‐( p ‐amylcinnamoyl) anthranilic acid (ACA),20 econazole, clotrimazole21 and 2‐aminoethoxydiphenyl borate (2‐APB) 22, 23. However, none of them show any specificity against TRPM2 channel 24.…”
Section: Introductionmentioning
confidence: 99%